Analysis Of Student Learning Independence On Blended Learning Model - Fadillah, Ahmad; Nopitasari, Dian; Bilda, Westi; Immawati, Siti Asriah; Raharjo, Sigit (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This research aims to describe students' learning independence in math learning in trigonometric materials. The method used in this study is a qualitative approach with descriptive methods. Participants in this study were students of SMK Avicena Tangerang Regency which amounted to 25 participants. The technique used in collecting data in this study is to provide a learning independence questionnaire consisting of 25 statements with 6 indicators. The data analysis technique used is with the student's answer percentage formula and is described using the criteria of interpreting the percentage of answers. The results of the analysis of each indicator of learning independence are: 1) Not dependent on others 78%, 2) Confidence 74%, 3) Disciplined behavior 70%, 4) Sense of responsibility 80%, 5) Learning initiative 72%, 6) Self-control 76%. The results showed that the overall average independence of students in learning by 75% with high categories. The results of this study provide recommendations to the school to support and optimize the improvement of student learning independence.Penelitian ini bertujuan untuk mendeskripsikan kemandirian belajar siswa pada pembelajaran matematika pada materi trigonometri. Metode yang digunakan dalam penelitian ini ialah pendekatan kualitatif dengan metode deskriptif. Partisipan dalam penelitian ini adalah siswa SMK Avicena Kabupaten Tangerang yang berjumlah 25 partisipan. Teknik yang digunakan dalam mengumpulkan data pada penelitian ini ialah dengan memberikan angket kemandirian belajar yang terdiri dari 25 pernyataan dengan 6 indikator. Teknik analisis data yang digunakan yaitu dengan rumus persentase jawaban siswa dan dideskripsikan menggunakan kriteria penafsiran presentase jawaban. Hasil analisis tiap indikator kemandirian belajar yaitu: 1) Tidak tergantung kepada orang lain 78%, 2) Kepercayaan diri 74%, 3) Perilaku disiplin 70%, 4) Rasa tanggung jawab 80%, 5) Inisiatif belajar 72%, 6) Pengendalian diri 76%. Hasil penelitian menunjukan bahwa rata-rata secara keseluruhan kemandirian siswa dalam belajar sebesar 75% dengan kategori tinggi. Hasil penelitian ini memberikan rekomendasi kepada pihak sekolah untuk mendukung dan mengoptimalkan peningkatan kemandirian belajar siswa.